Low dielectric loss in vanadium-based zircon ceramics via high-entropy strategy - Yuheng Zhang; Huaicheng Xiang; Xiaoyu Wu; Yang Zhou; Ying Tang; Liang Fang (Journal of Advanced Ceramics)
Zircon ceramics have potential applications in next-generation wireless communication because of their low permittivity and adjustable temperature coefficient at microwave frequencies. However, the vast challenge of realizing ultralow dielectric loss still exists. Here, we propose a high-entropy strategy to enhance the bonding of the A-site dodecahedron in zircon and design (Nd0.2Eu0.2Y0.2Ho0.2Yb0.2)VO4 ceramics with a high quality factor (high Q × f, that is, low dielectric loss). The (Nd0.2Eu0.2Y0.2Ho0.2Yb0.2)VO4 high-entropy ceramics, which belong to the tetragonal zircon structure with the I41/amd space group, exhibit a low relative permittivity (εr = 11.55), a negative temperature coefficient of resonant frequency (τf = −37.3 ppm/°C), and a high Q × f of 76,400 GHz (at 12.31 GHz). The high Q × f value can be attributed to the high chemical bond strength and structural stability. Furthermore, the relationship between the crystal structure and the microwave dielectric properties of (Nd0.2Eu0.2Y0.2Ho0.2Yb0.2)VO4 high-entropy ceramics was analyzed through high resolution transmission electron microscopy (HRTEM), Raman spectroscopy, far-infrared reflection spectroscopy, and chemical bond theory. This work provides an effective avenue for designing microwave dielectric materials with low loss to meet the demands of passive components.